Marine bacterial DNase curtails virulence and disrupts biofilms of Candida albicans and non-albicans Candida species. Issue 9 (21st October 2019) - Farisa Banu, Sanaulla; Thamotharan, Subbiah; Gowrishankar, Shanmugaraj; Karutha Pandian, Shunmugiah; Nithyanand, Paramasivam
Abstract: Candida is one of the most prevalent fungal pathogens in clinical settings which form antibiotic-resistant biofilms on biomedical devices. Hence, there is a need for non-antimicrobial alternatives to combat these infections. The present study investigates the anti-biofilm effect of marine bacterial DNase by targeting the eDNA present in the biofilms of Candida spp. A strain of Vibrio alginolyticus (AMSII) which showed enhanced DNase activity was isolated from marine sediment. Treatment of young and mature Candida biofilms with purified marine bacterial DNase (MBD) caused a 60-80% reduction in biofilm biomass, similar to treatment with DNase I from Bovine pancreas. Scanning electron microscopy showed that MBD significantly reduced the formation of biofilms on urinary catheters and more importantly prevented the virulent yeast to hyphae dimorphic switch in C. albicans . The present study identified a potential non-antibiotic alternative therapy to eradicate Candida biofilms and can be used to develop enzyme fabricated antifouling indwelling medical devices.